CAEP Dental Care Statement. Issue 1 (January 2020) - Sheikh, Hasan
ABSTRACT: Oral health is an important part of an individual's overall health; however, dental care is not included in the Canadian public healthcare system. Many Canadians struggle to access dental care, and six million Canadians avoid visiting the dentist each year due to cost. 1 The most vulnerable groups include children from low-income families, low-income adults, seniors, indigenous communities, and those with disabilities. 1 –5 The lack of affordable, equitable, and accessible dental care puts undue strain on emergency departments across the country, as patients desperately seek the care of a physician when they actually need the care of a dental professional. 6 Emergency physicians do not have the same expertise or equipment as dentists and, in most cases, are only able to provide temporary symptom relief. This results in an increased reliance on prescription opioids that would otherwise be unnecessary if patients could access the dental care they required.